2019
DOI: 10.1002/uog.20179
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal characteristics and gestational age on hemodynamic indices: NICOM device‐specific reference ranges

Abstract: Objectives To construct reference ranges for stroke volume, cardiac output and systemic vascular resistance (SVR) in normal pregnancy for the NICOM® device, and to explore associations between maternal characteristics and these hemodynamic variables. Methods This was a prospective cohort study of healthy singleton pregnancies between 10 and 40 weeks' gestation attending a tertiary referral hospital between September 2012 and May 2018. Measurements of stroke volume, cardiac output and SVR were obtained througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Prior studies have identified two distinct hemodynamic profiles based on the gestational age when pre‐eclampsia occurs: a hypodynamic profile with low CO, high TPR, and intravascular fluid depletion for early‐onset pre‐eclampsia and a hyperdynamic profile for late‐onset pre‐eclampsia 14,15 . Multiple maternal factors can influence the failure to achieve normal adaptive cardiovascular changes, increasing the risk of pre‐eclampsia and worsening maternal‐fetal outcomes 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have identified two distinct hemodynamic profiles based on the gestational age when pre‐eclampsia occurs: a hypodynamic profile with low CO, high TPR, and intravascular fluid depletion for early‐onset pre‐eclampsia and a hyperdynamic profile for late‐onset pre‐eclampsia 14,15 . Multiple maternal factors can influence the failure to achieve normal adaptive cardiovascular changes, increasing the risk of pre‐eclampsia and worsening maternal‐fetal outcomes 16 …”
Section: Discussionmentioning
confidence: 99%
“…maternal factors can influence the failure to achieve normal adaptive cardiovascular changes, increasing the risk of pre-eclampsia and worsening maternal-fetal outcomes. 16 No studies have assessed maternal hemodynamic adaptations in Latin American women, a unique population with significant racial mixing. 9 Our study found some differences.…”
Section: Discussionmentioning
confidence: 99%
“…; Perry et al . ). The latter data would indicate that maternal uterine perfusion dictates the degree of placental invasion rather than the other way round – a hypothesis which is consistent with cellular and mechanistic studies of trophobalsat function (Leslie et al .…”
Section: Cardiorenal Interactions In the Pathophysiology Of Preeclampsiamentioning
confidence: 97%
“…2). However, more recent evidence has demonstrated that uterine artery Doppler waveforms better reflect maternal systemic vascular resistance rather than local uterine artery resistance (Kalafat et al 2018;Perry et al 2018c). The latter data would indicate that maternal uterine perfusion dictates the degree of placental invasion rather than the other way round -a hypothesis which is consistent with cellular and mechanistic studies of trophobalsat function (Leslie et al 2015;Wallace et al 2015;James-Allan et al 2018;Charolidi et al 2019).…”
Section: Preconceptional Subclinical Cardiovascular Dysfunction Predimentioning
confidence: 99%
“…Measurements of cardiovascular parameters from the aortic root were performed in standardized conditions, as described previously 16,17 . In brief, women were positioned in a semi-recumbent position, and a USCOM-1A ® non-imaging probe (USCOM Ltd, Sydney, NSW, Australia) was used in the suprasternal notch to obtain VTI to derive indices.…”
Section: Cardiovascular Assessmentmentioning
confidence: 99%